Who wants to be a Millionaire?: An Analysis of Prosperity Teaching in the Charismatic Ministries (Churches) in Ghana and its Wider Impact - Anim, Emmanuel K. (LIT Verlag, 2020)
Prosperity Teaching is fast becoming a standard part of contemporary African Christianity. This teaching is best understood in the Charismatic and Pentecostal churches in Africa. The varied expressions and nuances call for a critical analysis of the phenomenon. Prosperity Teaching affirms wealth, divine healing, good health and long-life as manifestations of God's blessing. Conspicuous consumption is often seen as a sign of a successful life and suffering has no place in the divine order of God's sovereignty. This book, Who Wants to be a Millionaire? seeks to bring some understanding to this teaching and shows the extent of its impact in the wider society.